Sharing Session dengan Pelaku UMKM Obyek Wisata Baduy dalam Meningkatkan Daya Beli Wisatawan - Lina Marliana Dewi; Ratu Erlina Gentari; Deviyantoro Deviyantoro; Wahyuddin Wahyuddin (Nuras : Jurnal Pengabdian Kepada Masyarakat, 2026)
This Community Service (PkM) initiative aims to enhance the non-digital marketing capacity of MSME operators in the Baduy Dalam traditional tourism area by strengthening cultural storytelling, product display, service excellence, and interpersonal communication. The activities were conducted over 30 days using a participatory approach featuring sharing sessions and discussion forums involving 35 MSME operators. Needs assessment was carried out through seven days of participatory observation and interviews with 10 MSME operators. Evaluation results indicate an 80% program success rate, with a 70% increase in participant knowledge. Seven participants (70%) successfully applied cultural storytelling techniques, and eight participants (80%) were able to arrange product displays in accordance with the training material. These findings demonstrate that a non-digital marketing approach aligned with traditional values ​​contributes to enhancing the capacity of MSME operators to market their products in a more communicative and engaging manner. The program holds the potential to strengthen the competitiveness of local products while supporting the sustainability of cultural tourism in Kanekes Village.